Two-Photon Polymerization of 2.5D and 3D Microstructures Fostering a Ramified Resting Phenotype in Primary Microglia - Sharaf, Ahmed; Roos, Brian; Timmerman, Raissa; Kremers, Gert-Jan; Bajramovic, Jeffrey John; Accardo, Angelo (Frontiers in Bioengineering and Biotechnology, 2022)
Microglia are the resident macrophages of the central nervous system (CNS) and contribute to maintaining brain’s homeostasis. Current 2D “petri-dish” in vitro cell culturing platforms employed for microglia, are unrepresentative of the softness or topography of native brain tissue. This often contributes to changes in microglial morphology, exhibiting an amoeboid phenotype that considerably differs from the homeostatic ramified phenotype in healthy brain tissue. To overcome this problem, multi-scale engineered polymeric microenvironments are developed and tested for the first time with primary microglia derived from adult rhesus macaques. In particular, biomimetic 2.5D micro- and nano-pillar arrays (diameters = 0.29-1.06 µm), featuring low effective shear moduli (0.25-14.63 MPa), and 3D micro-cages (volume = 24x24x24 to 49x49x49 µm3) with and without micro- and nano-pillar decorations (pillar diameters = 0.24-1 µm) were fabricated using two-photon polymerization (2PP). Compared to microglia cultured on flat substrates, cells growing on the pillar arrays exhibit an increased expression of the ramified phenotype and a higher number of primary branches per ramified cell. The interaction between the cells and the micro-pillar-decorated cages enables a more homogenous 3D cell colonization compared to the undecorated ones. The results pave the way for the development of improved primary microglia in vitro models to study these cells in both healthy and diseased conditions.